Strategi Komunikasi Pemasaran Pada Ritel Elektronik Lokal: Studi Kualitatif di Plaza Bangunan 2 Lombok Timur - Agus Safari; M. Sahli; Jodi Hariawan; Alawi Hakiki (Journal Scientific of Mandalika (JSM) e-ISSN 2745-5955 | p-ISSN 2809-0543, 2026)
This study aims to analyze the marketing communication strategies implemented by local electronic retailers in marketing their products to consumers. The study employed a qualitative descriptive approach to obtain an in-depth understanding of communication practices at the grassroots business level. Data were collected through interviews with business owners and consumers, direct observation of sales activities, and documentation related to promotional practices. The research was conducted at Plaza Gedung 2 in East Lombok Regency, which represents a typical local electronic retail business environment.The results show that marketing communication strategies are primarily implemented through direct and face-to-face interactions with consumers. Retailers emphasize personalized delivery of product information, including explanations of product features, usage, pricing, and after-sales services. In addition, simple promotional media such as verbal promotions and informal recommendations are used and adapted to the characteristics, needs, and purchasing power of consumers. These strategies play an important role in building consumer understanding, trust, and purchasing confidence. However, the communication efforts are generally not structured within formal or documented marketing plans. Overall, the findings indicate that marketing communication in local electronic retailers is practical, adaptive, and highly dependent on the interpersonal communication skills and experience of business actors in engaging with consumers